The triglyceride and glucose index and risk of nonalcoholic fatty liver disease: A dose–response meta-analysis - Ling, Qin; Chen, Jiawei; Liu, Xiao; Xu, Yi; Ma, Jianyong; Yu, Peng; Zheng, Kai; Liu, Fuwei; Luo, Jun (Frontiers in Endocrinology, 2023)
Background: The triglyceride and glucose (TyG) index is associated with the risk of nonalcoholic fatty liver disease (NAFLD), but the dose‒response relationship between them is still unknown. We conducted a comprehensive meta-analysis to study the dose‒response association between the TyG index and the risk of NAFLD. Methods: We systematically searched the Cochrane Library, PubMed, and Embase databases until July 2022 for relevant studies. The robust error meta-regression method was used to investigate the dose‒response association between the TyG index and NAFLD. Summary relative risks (ORs) and 95% CIs were estimated by using a random-effects model. Results: A total of 4 cohort and 8 cross-sectional studies were included, with 28,788 NAFLD cases among the 105,365 participants. A positive association for the risk of NAFLD was observed for each additional unit of the TyG index with a linear association (p=0.82), and the summary OR was 2.84 (95% CI, 2.01-4.01). In the subgroup analyses, a stronger association of the TyG index with NAFLD was shown in females than in males (men: OR=2.97, 95% CI 2.55-3.46, women: OR=4.80, 95% CI 3.90-5.90, Psubgroup<0.001). Conclusion: The TyG index may be a novel independent risk factor for NAFLD beyond traditional risk factors.